2020
DOI: 10.1097/pr9.0000000000000832
|View full text |Cite
|
Sign up to set email alerts
|

The association between daily physical exercise and pain among women with fibromyalgia: the moderating role of pain catastrophizing

Abstract: Daily physical exercise is associated with more self-reported pain intensity in women with fibromyalgia pain, particularly among those with higher levels of pain catastrophizing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 56 publications
(59 reference statements)
1
17
0
Order By: Relevance
“…It is well known that catastrophizing plays an important role in the syndromes of fibromyalgia and chronic low back pain with respect to prevalence and the severity of pain (Angarita‐Osorio et al, 2020; Catala et al, 2020; Écija et al, 2020; Edwards et al, 2006; Fillingim et al, 2020; Galvez‐Sánchez et al, 2020; Lazaridou et al, 2020; Marshall et al, 2017; Othman et al, 2020; Pulido‐Martos et al, 2020; Wertli, Burgstaller, et al, 2014; Wertli, Eugster, et al, 2014). Relatively high levels of perceived disease severity compared to other chronic pain conditions are reported for fibromyalgia (Angst et al, 2021; Bucourt et al, 2021; Fillingim et al, 2020; Salaffi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that catastrophizing plays an important role in the syndromes of fibromyalgia and chronic low back pain with respect to prevalence and the severity of pain (Angarita‐Osorio et al, 2020; Catala et al, 2020; Écija et al, 2020; Edwards et al, 2006; Fillingim et al, 2020; Galvez‐Sánchez et al, 2020; Lazaridou et al, 2020; Marshall et al, 2017; Othman et al, 2020; Pulido‐Martos et al, 2020; Wertli, Burgstaller, et al, 2014; Wertli, Eugster, et al, 2014). Relatively high levels of perceived disease severity compared to other chronic pain conditions are reported for fibromyalgia (Angst et al, 2021; Bucourt et al, 2021; Fillingim et al, 2020; Salaffi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge, there are few studies exploring specifically how catastrophizing influences physical activity and exercise or walking. Recently, Lazaridou and colleagues [41], using electronic diaries and a step count, found that increases in daily physical activity was associated with more pain intensity in women with fibromyalgia, mainly in those with a higher rate of catastrophizing. Hence, pain catastrophizing shows different ways of influence on physical activity and it is worth conducting further research about its role on walking exercise, mainly considering new recommendations about its assessment [31].…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of catastrophizing in chronic pain and fibromyalgia has been highlighted [34][35][36][37][38][39][40]. Recently, some authors have shown pain catastrophizing as a moderator in fibromyalgia pain intensity and physical activity relationships [41]. However, to the best of our knowledge, little is known about its role in undertaking and, mainly, maintaining walking exercise, taking into account its possible influence on habitual patients' goal preferences.…”
Section: Introductionmentioning
confidence: 99%
“…For people with MS, a Beurer AS 80 and Yamax SW 200 Digiwalker were used to determine cross sectional associations of serum vitamin D levels and activity capacity with daily PA levels [ 42 , 43 ]. For individuals who experienced gout flares, were in the early stages of PD, were stroke survivors, and experience fibromyalgia, step counts and time spent in MVPA from a Fitbit device worn for ≥ 7 days was used to measure PA levels [ 39 , 41 , 44 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ActConnect study explored factors associated with lower PA in individuals with RA and axial spondyloarthritis using a smartwatch [36] [42,43]. For individuals who experienced gout flares, were in the early stages of PD, were stroke survivors, and experience fibromyalgia, step counts and time spent in MVPA from a Fitbit device worn for ≥ 7 days was used to measure PA levels [39,41,[44][45][46].…”
Section: Feasibility and Utility Of Implementing Consumer Wearables In Clinical Populationsmentioning
confidence: 99%